EFISIENSI KEBIJAKAN MONETER DI INDONESIA DENGAN PENDEKATAN MODEL CECCHETTI DAN KRAUSE - Putri, Meylinda Sulfiana; Wahyuningsih, Diah (Universitas Nusantara PGRI Kediri, 2016)
This study is aimed to measure the efficiency of the implementation of monetary policy in Indonesia in the period of 1999:1 – 2015:2 with Cecchetti and Krause (2002) model approach by using loss function method. Estimation method used in this study is autoregressive dynamic model with two linear equations (industrial production function and the function of inflation). The first equation is production function with dependent variable is log industrial production and independent variables are the BI Rate, the inflation, the log industrial production, and log external prices inflation (the ratio of export import). As the second equation is the function of inflation where the dependent variable is inflation and the independent variables are log industrial production, inflation, and external prices inflation (the ratio of export import). The research results showed the monetary policy in Indonesia in the long term is relatively more efficient than short term. It is proven by the fluctuations in the loss function on the efficiency frontier curve where the value of the loss function is closer to the origin and in the frontier area in the long term which shows that the monetary policy is relatively more efficient. In the long term, the value of the loss function of inflation is 7,9712 and loss function of production is 0,0382. Whereas, in the short term, the value of the loss function of production is 0,6808 and inflastion is 9,4325.